Urban development in arid regions: A comparative study of Masdar City and the new town of Hassi Messaoud - Bensehla Sofiane (Glasnik Srpskog Geografskog Društva)
Rapid urbanization worldwide poses significant challenges in creating resilient urban environments, particularly in arid regions. This study examines the development of sustainable urban environments in desert climates through a comparative analysis of two distinct cities: Masdar City in the United Arab Emirates and the New Town of Hassi Messaoud in Algeria. Masdar City represents a high-tech, globally oriented model that integrates advanced technologies, renewable energy, and innovative urban planning to achieve a zero-carbon urban hub. In contrast, the New Town of Hassi Messaoud adopts a regionally focused, socially inclusive approach, emphasizing thermal comfort, cultural identity, and the relocation of populations at risk due to industrial activities. By analysing their urban planning, economic strategies, social dynamics, and environmental sustainability, this study highlights the unique opportunities and challenges of desert urbanization. Key findings reveal that Masdar City excels in technological innovation and renewable energy integration but faces gaps in social infrastructure, while Hassi Messaoud prioritizes social equity and traditional design but encounters challenges in energy efficiency and funding limitations. The study underscores the importance of balancing technological advancements with social inclusivity, integrating traditional and modern practices, and adopting adaptive, holistic approaches to urban development. Lessons learned from these case studies provide valuable insights for future urbanization and climate strategies, particularly in arid regions, emphasizing the need for equitable, resilient, and sustainable cities capable of addressing the interconnected challenges of rapid urbanization and climate change.